USING OF FREQUENCY MODELS FOR TECHNICAL DIAGNOSTICS DISREPAIRS OF METALLURGICAL EQUIPMENT - Hrechanyi , Oleksii; Kobrin , Yuri; Vasilchenko , Tatiana; Ignatiev , Aleksandr; Kuzmenko , Rаdyslav; Shevchenko, Irene (Scientific Journal "Metallurgy", 2020)
The main objective of technical diagnostics is the logical continuation and development of control tasks, that is, the purpose of monitoring and diagnostics is aimed at determining in which of a predetermined set of conditions the object under investigation is located. The diagnostic procedure itself contains a certain set of control operations of the entire object as a whole, as well as its individual elements. In this case, it is necessary to determine which of the operations need to be carried out and in what sequence, how, in order to specify the malfunction, to process the results of these operations. Modeling is one of the most reliable methods and effective research tools for both simple and complex technical systems, at all stages of their life cycle. In order to reduce the volume of expensive and lengthy experimental studies, it is advisable to carry out diagnostic modeling of defects, that is, a physical or diagnostic interpretation of the relationship between the state space and the space of diagnostic signs is established using the diagnostic model of the object. Kinematic analysis applying to the problems of vibration diagnostics consists in determining the angular speeds of rotation (or frequencies) of individual parts of the mechanism, depending on the frequency of rotation of the electric motor. Frequency modeling is based on the polyharmonic representation of oscillations whose frequency is determined with the frequency of manifestation of defects. The purpose of frequency modeling is to identify the rotational speeds of all the moving elements of the machines, including the frequency of the teeth and the rotational speed of the elements of the rolling bearings (rolling elements, rings, cage). The possibility of using frequency models as diagnostic models for metallurgical equipment using the example of a sheet straightening machine is considered. The influence of the operating speeds of the electric motor of the drive of the sheet straightening machine on its overall performance is established. The obtained frequency map of defects of the drive unit allows the analysis of various diagnostic features for drive failures of the plate straightening machine.